2022
DOI: 10.3389/fonc.2022.807266
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Metabolic Landscape of AML: From Haematopoietic Stem Cells to Myeloblasts and Leukaemic Stem Cells

Abstract: Despite intensive chemotherapy regimens, up to 60% of adults with acute myeloid leukaemia (AML) will relapse and eventually succumb to their disease. Recent studies suggest that leukaemic stem cells (LSCs) drive AML relapse by residing in the bone marrow niche and adapting their metabolic profile. Metabolic adaptation and LSC plasticity are novel hallmarks of leukemogenesis that provide important biological processes required for tumour initiation, progression and therapeutic responses. These findings highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 160 publications
(267 reference statements)
1
29
0
Order By: Relevance
“…The intramitochondrial FAO enzyme very long-chain acyl-CoA dehydrogenase (VLCAD) is critical in supporting both FAO and OXPHOS in AML cells and LSCs. Recently, preclinical studies have demonstrated the antileukemia activity of a novel small-molecule VLCAD inhibitor, a polyhydroxylated fatty alcohol with a terminal alkyne (AYNE) [95] . AYNE reduced mitochondrial respiration by altering FAO, which led to reduced ATP production in AML cells, even though AYNE also moderately upregulated glycolysis.…”
Section: Fao Of Aml Cells In the Bm Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The intramitochondrial FAO enzyme very long-chain acyl-CoA dehydrogenase (VLCAD) is critical in supporting both FAO and OXPHOS in AML cells and LSCs. Recently, preclinical studies have demonstrated the antileukemia activity of a novel small-molecule VLCAD inhibitor, a polyhydroxylated fatty alcohol with a terminal alkyne (AYNE) [95] . AYNE reduced mitochondrial respiration by altering FAO, which led to reduced ATP production in AML cells, even though AYNE also moderately upregulated glycolysis.…”
Section: Fao Of Aml Cells In the Bm Microenvironmentmentioning
confidence: 99%
“…AYNE reduced mitochondrial respiration by altering FAO, which led to reduced ATP production in AML cells, even though AYNE also moderately upregulated glycolysis. In a mouse model, pharmacological inhibition of VLCAD with AYNE significantly reduced the repopulation potential of leukemia cells and was well tolerated [95] . Notably, normal HSCs compensate for this reduced replicative capacity through glycolysis which maintains their ATP levels and thus their viability [95,96] .…”
Section: Fao Of Aml Cells In the Bm Microenvironmentmentioning
confidence: 99%
“…Recently, Aasebø et al, using liquid chromatography-tandem mass spectrometry (LC-MS/MS), compared proteomic and phosphoproteomic profiles of AML cells derived from AML patients at the time of first diagnosis as well as at first relapse, and found significant enrichment of mitochondrial ribosomal subunit proteins, mitochondrial respiratory chain complex proteins, and proteins involved in mitochondrial metabolism, and higher phosphorylation level of nucleolar as well as nucleic-acid-binding metabolism proteins at first relapse [ 158 ]. This raises the possibility that drug-resistant, relapse-initiating LSCs may exploit mitochondrial dynamics to possibly reconcile survival and self-renewal with a predominantly quiescent state [ 159 ]. Specifically, AML LSCs are known to preferentially rely on oxidative phosphorylation (OXPHOS) as opposed to glycolysis to maintain cellular bioenergetics, and have managed to use BCL-2-depedent mechanisms to keep the production of reactive oxygen species (ROS), byproducts of OXPHOS, at bay, which is in alignment with their slowly proliferating, quiescent properties [ 160 , 161 ].…”
Section: Cell-intrinsic Signaling: Aberrant Multi-omics Circuitry Of ...mentioning
confidence: 99%
“…First discovered in AML in the 1990s, LSC represent a small subpopulation of abnormal leukemia cells which sustain tumorigenesis by their various self-renewal properties ( 51 ). These anomalous cells maintain their quiescence by remaining hidden within the bone marrow, which shields them from chemotherapy, corruptive reactive oxygen species and the anaerobic metabolism ( 53 ). It is hypothesized that healthy HSC can give rise to new leukemic clones after acquiring sufficient genetic mutations ( 54 ).…”
Section: Leukemic Stem Cells (Lsc)mentioning
confidence: 99%
“…With the help of DNA-sequencing, the study identified cells carrying pre-malignant mutations and malignant mutations such as CEBPA and NPM1 . Recent studies have demonstrated that LSCs are prone to express various surface markers such as CD32, CD44, CD47, CD123, TIM3, CD45RA and CD96 ( 53 ). Haubner et al analyzed the expression profile of LSCs in AML patients (n=356) and discovered that CD123 (97.0%), CD244 (96.7%), CD33 (96.4%), TIM3 (87.3%) and CLL1 (80.1%) were the most common surface markers ( 56 ).…”
Section: Leukemic Stem Cells (Lsc)mentioning
confidence: 99%